Diversity and pathogenicity of the rice brown spot pathogen, Bipolaris oryzae (Breda de Haan) Shoem. in Bangladesh assessed by genetic fingerprint analysis (Bangladesh Journal of Botany, 2010)
A survey on the occurrence of rice brown spot pathogen, Bipolaris oryzae (Breda de Haan) Shoem. was carried out across Bangladesh. A representative set of 152 isolates were characterized based on DNA fingerprinting, using variable number tandem repeat analysis and assessed their phylogenetic identity, diversity and pathogenicity. The analysis showed considerable diversity among the isolates, being separated into 12 fingerprint types at 75% similarity level. Majority of the samples possessed one fingerprint type. Pathogenicity test with nine fingerprint types on rice variety BR24, showed 20.5-84.5% germination failure, 2.50-12.50, 5.84-11.67 and 7.50-14.17% post-emergence seedling death at 15, 30 and 45 days after transplanting and 18.75-22.50% yield loss. Significant differences in aggressiveness were observed among the isolates of the same fingerprint types.   Key words: Bipolaris oryzae; Rice brown spot; Pathogenicity; Agarose-synergel; Fingerprints DOI: 10.3329/bjb.v38i2.5135 Bangladesh J. Bot. 38(2): 119-125, 2009 (December)